Kepemimpinan Spiritual Kepala Sekolah dalam Menanamkan Budaya Religius di Sekolah Dasar Negeri Jurangsapi 1, Tapen, Bondowoso - Mokhamad Yaurizqika Hadi; Nur Ittihadatul Ummah (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2020)
This study discusses the Principal's Spiritual Leadership in Instilling Religious Culture in Jurangsapi 1 Elementary School, Tapen District, Bondowoso Regency. The principal is one of the important factors that determines school success because the principal is a vital organ in the school ecosystem, especially in public primary schools that have fewer religious activities than religious or religious schools so it needs to be balanced with the inculcation of religious culture so that religious values ​​remain embedded in students. This study aims to determine: (1) Principal's spiritual leadership in vision aspects in instilling religious culture (2) Principal's spiritual leadership in altruistic love in instilling religious culture (3) Principal's spiritual leadership in hope (aspects hope) in instilling religious culture. Data collection techniques using semi-participant observation, semi-structured interviews and documentation. Analysis of the data used is the qualitative data analysis of Milles and Huberman's interactive models, while the validity of the data used is the triangulation of sources and techniques. The results of this study indicate that: (1) Principal's Spiritual Leadership in the Aspect of Vision in Embedding Religious Culture ie the principal as a spiritual leader in instilling religious culture shows a vision of a strong spiritual leadership by involving all school stakeholders , defines the purpose of the school as the ideals of the principal, as well as encouraging expectations in a superior school standard, namely state primary schools with religious nuances. (2) Principal's Spiritual Leadership in the Altruistic Love Aspect in Instilling Religious Culture, namely the Principal as a spiritual leader promotes altruistic love (3) The Principal's Spiritual Leadership in the Hope Aspect (Instilling) in Instilling Religious Culture. The principal as a spiritual leader in realizing his ideals shows strong expectations. Penelitian ini membahas tentang Kepemimpinan Spiritual Kepala Sekolah dalam Menanamkan Budaya Religius di Sekolah Dasar Negeri Jurangsapi 1 Kecamatan Tapen Kabupaten Bondowoso. Kepala sekolah merupakan salah satu faktor penting yang menentukan keberhasilan sekolah karena kepala sekolah adalah organ vital dalam ekosistem sekolah, terlebih pada sekolah dasar negeri yang memiliki kegiatan agama lebih sedikit dibanding sekolah agama atau keagamaan sehingga perlu diimbangi dengan penanaman budaya religius agar nilai-nilai agama tetap tertanam pada diri peserta didik. Penelitian ini bertujuan untuk mengetahui: (1) Kepemimpinan spiritual kepala sekolah aspek visi (vision) dalam menanamkan budaya religius (2) Kepemimpinan spiritual kepala sekolah aspek cinta altruistik (altruistic love) dalam menanamkan budaya religius (3) Kepemimpinan spiritual kepala sekolah aspek harapan (hope) dalam menanamkan budaya religius. Teknik pengumpulan data menggunakan jenis observasi semi partisipan, wawancara semi terstruktur dan dokumentasi. Analisis data yang digunakan yaitu analisis data kualitatif model interaktif Milles dan Huberman, sedangakan keabsahan data yang digunakan adalah triangulasi sumber dan teknik. Hasil dari penelitian ini menunjukan bahwa : (1) Kepemimpinan Spiritual Kepala Sekolah pada Aspek Visi (vision) dalam Menanamkan Budaya Religius yakni kepala sekolah sebagai pemimpin spiritual dalam menanamkan budaya religius menunjukan visi (vision) kepemimpinan spiritual yang kuat dengan mengikut sertakan seluruh stake holder sekolah, mendefinisikan tujuan sekolah sebagai cita-cita kepala sekolah, serta mendorong harapan pada standart sekolah yang unggul yaitu sekolah dasar negeri yang bernuansa religius. (2) Kepemimpinan Spiritual Kepala Sekolah pada Aspek Cinta Altruistik (altruistic love) dalam Menanamkan Budaya Religius yakni Kepala sekolah sebagai pemimpin spiritual mengedepankan cinta altruistik (3) Kepemimpinan Spiritual Kepala Sekolah pada Aspek Harapan (hope) dalam Menanamkan Budaya Religius. Kepala sekolah sebagai pemimpin spiritual dalam mewujudkan cita-citanya menunjukan harapan yang kuat. Kata Kunci: kepemimpinan spiritual kepala sekolah, budaya religious, sekolah dasar